Longitudinal profiling of plasma and urine metabolites during liver regeneration in living liver donors. Issue 1 (1st October 2021) - Bottiglieri, Teodoro; Wang, Xuan; Arning, Erland; Fernandez, Hoylan; Wall, Anji; McKenna, Greg; Ruiz, Richard; Onaca, Nicholas; Trotter, James; Lawrence, Michael; Naziruddin, Bashoo; Asrani, Sumeet K.; et al.
Abstract: Background: Knowledge of metabolic processes affected by major hepatectomy (MHx), and the metabolic pathways involved in liver regeneration and recovery of function, is limited and mainly derived from animal models. Assessment of restoration of hepatic function is essential in human living liver donors (LD). Methods: We used a targeted metabolomic approach to longitudinally quantify changes in plasma and urine biomarkers from healthy LD. The biomarkers were analyzed before MHx and at scheduled intervals up to 12 months thereafter. Results: Marked changes were found in the concentration of 15 primary and secondary plasma bile acids. Most significant changes occurred 2 days after MHx and persisted for up to 3 months. In addition, there were significant changes in acylcarnitine, phospholipid, and amino acid metabolism. The sum of aromatic amino acids and the Fischer ratio, both metabolic markers of liver damage, and the symmetrically demethylated arginine to arginine ratio, a marker of kidney function, were affected. Conclusions: This is the first comprehensive longitudinal study investigating metabolic processes during recovery of liver function after MHx in LD. It provides further evidence of full restoration of metabolic processes 3 months after MHx and supports future investigation to understand how metabolic changes affect donors' hepatic function.